The impact of governance on the reputation of the organization - ahmed abdulkreem1, Sarah; kadhm saeed, Hadeel (Journal of Economics and Administrative Sciences, 2020)
The current study aims to determine the extent of SOMO's interest in governance and whether this interest is sufficient to be reflected in enhancing its organizational reputation, and the field of research was in the oil marketing company SOMO. (109), (105) questionnaires were distributed, (94) forms and (11) forms were not retrieved, and the valid questionnaires had reached (91). The analytical and descriptive approach was used for the study, and the current research has found a positive impact of government on the reputation of the organization, and this research demonstrated the existence of the proposed relationship and the impact between governance and the reputation of the organization.